THE ROLE OF BAITUL MAAL WAT TAMWIL (BMT) TO IMPROVE THE COMMUNITY'S ECONOMY (EL MUDHORIB : Jurnal Kajian Ekonomi dan Perbankan Syariah, 2022)
Baitul Maal Wat Tamwil (BMT) has an important role in realizing the economic improvement of the community. But not all people know the special part of BMT. So many people prefer to go to the bank. The purpose of this paper is to find out the role of BMT and the impact caused by the presence of BMT. This writing uses the literature review method with a data collection method using books and previous articles. The results of this paper show that the role of BMT is to make people switch to Sharia transaction activities. Meanwhile, the impact caused by the presence of BMT is to make it easier to develop micro / small businesses that need funds for their business.